Do Foreign Direct Investment Inflows Impinge Gross Domestic Product? A Venture Out for ASEAN - Nida Rahman; Mohd. Nayyer Rahman (Jurnal Ekonomi dan Studi Pembangunan, 2018)
Foreign Direct Investment, since decades, has taken over other sources of debt flows both in developed as well as emerging economies of the world. The reason that support this overly attachment to revered flows of FDI does not seem to benign the economies by smidgens but in amass. Back to 1990s, the economies over the world witnessed huge opening of their foreign policies with an avarice objective of luring more and more foreign capital, more advancely, foreign investment. The globalisation phenomenon that also gauges back to the late 80s and early 90s saw in the opening up of economies a plethora of opportunities to integrate economies across the globe. One major instance of the speeding globalisation was seen in the form of bilateral and multilateral agreements among nations to enhance cooperation on mutual fronts. ASEAN, one such conglomeration, saw its inception back in 1967 and with the steering of global identity, the participating members extended from five founding members to other countries of Southeast Asia as well. The ameliorating figure of Foreign Direct Investment Inflows in the ASEAN region has stirred a need for quantifying the overall effect of FDI Inflows on Gross Domestic Product of the region. The present research note intends to capture this impingement of Foreign Direct Investment Inflows on Gross Domestic Product of the Ten Southeast Asian member nations which together constitute ASEAN. The data is fetched from UNCTAD Statistics database for a time range of 1980-2015. Panel regression technique is deployed to meet ends. The results of the econometric approach of Random Effects Panel Regression indicate a significant and positive impingement of Foreign Direct Investment Inflows on Gross Domestic Product of ASEAN member states. The outcome of the analysis thus throws light on how Foreign Direct investment Inflows has contributed to the Gross Domestic product of ASEAN and further exploration in the area will blossom the relationship. Keywords: Foreign Direct Investment Inflows, ASEAN, UNCTAD.JEL Classification: F10, F21